Error estimates for scalar conservation laws by a kinetic approach - A. Omrane (International Journal of Mathematics and Mathematical Sciences)
We use the kinetic approach of Perthame and Tadmor (1991) to calculate the error estimates for general scalar conservation laws governing problems in gas dynamics or fluid mechanics in general. The Kružkov and Kuznetsov techniques are generalized to this method, and an error bound of order ε (where ε is the mean free path) is obtained.